Lead Concentration In Soils Of Roadside Farmland In Lubuk Pakam, Deli Serdang - Devi Nuraini Santi; Indra Chahaya; Winni R.E. Tumanggor (Universitas Islam Negeri Sumatera Utara, Medan, 2023)
Health issues are a concern of the current government. Health issues are in line with the economic development that the government is aggressively prioritizing. This economic improvement certainly requires a variety of supporting infrastructure. One of them is road infrastructure. Adequate road infrastructure will certainly increase traffic activity. Traffic activity is one of the sources of heavy metal pollution in soil. The contents of motor vehicle emission gases is lead. Lead (Pb) is one of the metal elements that can cause poisoning in humans. This research is important to determine the concentration of soil which is an area of agricultural land that is overgrown with rice. This research was conducted to investigate lead concentration in roadside farmland soils according to roadside distance in the street of Lubuk Pakam - Medan km 32. A total of 13 topsoils samples were collected with a distance of 0 m, 5 m, 20 m, 40 m, 50 m, 60 m, 80 m, 100 m, 120 m, 150 m, 200 m, 250 m, and 300 m from the roadside. The study found that the consentration of lead in the soil was in the range of 2.33-11.40. There is no correlation of lead concentration in soil with distance from highway with r =0.093 and p=0,762. The land farm lead-contaminated if used to grow crops that will be consumed is at risk of lead-contaminated Keyword: Lead concentration, Traffic activity, Pollution